Cerebrospinal Fluid Viral Load Across the Spectrum of Untreated Human Immunodeficiency Virus Type 1 (HIV-1) Infection: A Cross-Sectional Multicenter Study. (8th November 2021) - Ulfhammer, Gustaf; Edén, Arvid; Antinori, Andrea; Brew, Bruce J; Calcagno, Andrea; Cinque, Paola; De Zan, Valentina; Hagberg, Lars; Lin, Amy; Nilsson, Staffan; Oprea, Cristiana; Pinnetti, Carmela; et al.
Abstract: Background: The aim of this large multicenter study was to determine variations in cerebrospinal fluid (CSF) HIV-RNA in different phases of untreated human immunodeficiency virus type 1 (HIV-1) infection and its associations with plasma HIV-RNA and other biomarkers. Methods: Treatment naive adults with available CSF HIV-RNA quantification were included and divided into groups representing significant disease phases. Plasma HIV-RNA, CSF white blood cell count (WBC), neopterin, and albumin ratio were included when available. Results: In total, 1018 patients were included. CSF HIV-RNA was in median (interquartile range [IQR]) 1.03 log10 (0.37–1.86) copies/mL lower than in plasma, and correlated with plasma HIV-RNA (r = 0.44, P < .01), neopterin concentration in CSF (r = 0.49, P < .01) and in serum (r = 0.29, P < .01), CSF WBC (r = 0.34, P < .01) and albumin ratio (r = 0.25, P < .01). CSF HIV-RNA paralleled plasma HIV-RNA in all groups except neuroasymptomatic patients with advanced immunodeficiency (CD4 < 200) and patients with HIV-associated dementia (HAD) or opportunistic central nervous system (CNS) infections. Patients with HAD had the highest CSF HIV-RNA (in median [IQR] 4.73 (3.84–5.35) log10 copies/mL). CSF > plasma discordance was found in 126 of 972 individuals (13%) and varied between groups, from 1% in primary HIV, 11% in neuroasymptomatic groups, up to 30% of patients with HAD. Conclusions: Our study confirms previous smaller observations of variations in CSF HIV-RNA in different stages of HIV disease. Overall, CSF HIV-RNA was approximately 1 log10 copies/mL lower in CSF than in plasma, but CSF discordance was found in a substantial minority of subjects, most commonly in patients with HAD, indicating increasing CNS compartmentalization paralleling disease progression. Abstract : HIV-RNA is detectable in cerebrospinal fluid (CSF) across all stages of untreated HIV and usually parallel plasma HIV-RNA at a lower level. A substantial proportion (13%) of patients have CSF>plasma HIV-RNA, most commonly in patients with HIV-associated dementia.